Methods of modelling of socio-economic phenomena: semiotic and chain analyses - Shcherbin, Vyacheslav K. (Journal of the Belarusian State University. Sociology, 2021)
The article considers the methods of semiotic modelling (semiotic and chain analyses). The relevance of the use of these methods for the study of socio-economic phenomena is determined. Features of the use of these methods are described on the material of two groups of chains: the group of communicative, speech, textual chains, chains of motifs, etc.; the group of economic, knowledge, linguistic, philosophical, social, technological, value chains, etc. Differences between considered methods are caused not only by the material, for description of which they are used, but also by other its attributes: a) by its different aims and objects of researchers, in which these methods are used. The purpose of semiotic analysis is to model complex signs for a more thorough understanding of socio-economic phenomena in general, representing such phenomena as sign systems (codes, texts, discourses). The object of chain analysis is socio-economic chains of different types, throughthe modelling of which various social and economic relations forming the basis of social-economic picture of the world are studied; b) by its key concepts, which form the notional basis of such methods. Key concepts of the semiotic analysis are a concept «code» and a concept «text»; for the chain analysis – a concept «chain link» and a concept «chain». The conclusion is substantiated about the inclusion of semiotic and chain analyses, side by side with other methods of the semiotic modelling (for example, such as method of constructing multiple spirals, multimodal analysis, method of synectics etc.) to a structure of methodological basis of the new direction of sociology – the social semiotics.
Keywords: method; modelling; types of models; simple and complex signs; systems of signs; code; text; semiotic analysis; chain analysis; socio-economic phenomena; socio-economic chains